Recruitment of hypothalamic orexin neurons after formalin injections in adult male rats exposed to a neonatal immune challenge - Campbell, Erin J.; Watters, Stephanie M.; Zouikr, Ihssane; Hodgson, Deborah M.; Dayas, Christopher V. (Frontiers in Neuroscience, 2015)
Exposure to early life physiological stressors, such as infection, is thought to contribute to the onset of psychopathology in adulthood. In animal models, injections of the bacterial immune challenge, lipopolysaccharide (LPS), during the neonatal period has been shown to alter both neuroendocrine function and behavioural pain responses in adulthood. Interestingly, recent evidence suggests a role for the lateral hypothalamic peptide orexin in stress and nociceptive processing. However, whether neonatal LPS exposure affects the reactivity of the orexin system to formalin-induced inflammatory pain in later life remains to be determined. Male Wistar rats (n=13) were exposed to either LPS or saline (0.05mg/kg, i.p) on postnatal days (PND) 3 and 5. On PND 80-97, all rats were exposed to a subcutaneous hindpaw injection of 2.25% formalin. Following behavioural testing, animals were perfused and brains processed for Fos-protein and orexin immunohistochemistry. Rats treated with LPS during the neonatal period exhibited decreased licking behaviours during the interphase of the formalin test, the period typically associated with the active inhibition of pain, and increased grooming responses to formalin in adulthood. Interestingly, these behavioural changes were accompanied by an increase in the percentage of Fos-positive orexin cells in the dorsomedial and perifornical hypothalamus in LPS-exposed animals. Similar increases in Fos-protein were also observed in stress and pain sensitive brain regions that receive orexinergic inputs. These findings highlight a potential role for orexin in the behavioural responses to pain and provide further evidence that early life stress can prime the circuitry responsible for these responses in adulthood.